PENGARUH KUALITAS LAYANAN, KEPERCAYAAN, LITERASI KEUANGAN SYARIAH, DAN KEPUASAN TERHADAP KEPUTUSAN NASABAH MEMILIH BANK SYARIAH - Syahrul Fadhillah Achmad; Jaharuddin Jaharuddin (Media Riset Bisnis Manajemen Akuntansi, 2025)
The growth of the Islamic banking industry in the digital era demands a deeper understanding of the factors influencing customer decision-making, especially among younger generations. This study aims to examine the extent to which trust, Islamic financial literacy, and customer satisfaction affect the decision of customers to use Islamic banking services.A quantitative approach was employed using a survey method, with data collected from 122 Islamic bank customers in South Tangerang through an online questionnaire. The data were analyzed using Structural Equation Modeling (SEM) based on the Partial Least Square (PLS) technique. The results reveal that trust and Islamic financial literacy significantly influence satisfaction but do not directly affect customer decisions. In contrast, satisfaction has a significant impact on decision-making regarding the use of services. These findings highlight the critical role of delivering a satisfying customer experience as a key driver of customer decisions. This research contributes to the development of Islamic consumer behavior theory and offers practical implications for improving service quality in Islamic banking. Future research is recommended to examine mediation and moderation variables to gain a more comprehensive understanding.Keywords: Trust; Islamic Financial Literacy; Satisfaction, Customer Decision; Islamic Bank